2012
DOI: 10.1109/tvcg.2012.197
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Using Visual Embellishments in Visualization

Abstract: In written and spoken communications, figures of speech (e.g., metaphors and synecdoche) are often used as an aid to help convey abstract or less tangible concepts. However, the benefits of using rhetorical illustrations or embellishments in visualization have so far been inconclusive. In this work, we report an empirical study to evaluate hypotheses that visual embellishments may aid memorization, visual search and concept comprehension. One major departure from related experiments in the literature is that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 32 publications
8
103
0
Order By: Relevance
“…Similar studies have been conducted to better understand the effect of visual embellishments, but the results are mixed: most of the time they do not seem to negatively affect the correct perception of information from the visualization [3,38]. Borkin et al ran a large-scale online study to identify design elements that make a visualization easier to recognize and found that aesthetic factors may play a major role [5] on which charts are more easily memorized, even though the study did not consider the actual content of the charts.…”
Section: Visualization Impactmentioning
confidence: 88%
“…Similar studies have been conducted to better understand the effect of visual embellishments, but the results are mixed: most of the time they do not seem to negatively affect the correct perception of information from the visualization [3,38]. Borkin et al ran a large-scale online study to identify design elements that make a visualization easier to recognize and found that aesthetic factors may play a major role [5] on which charts are more easily memorized, even though the study did not consider the actual content of the charts.…”
Section: Visualization Impactmentioning
confidence: 88%
“…8. A noticeable variation is visible across markers, the Friedman's test showed a significant main effect in both accuracy (χ 2 • Mean Response Time -OOMM1 markers (mean = 17.95) were significantly slower than linear (mean = 11.22) and significantly faster than scale-stack bar (mean = 24.71) (p 0.002). As OOMM1 markers are slower but more accurate than linear, a correlation test of time vs. accuracy was performed to detect any trade-off effect.…”
Section: Main Study Analysismentioning
confidence: 95%
“…Other studies revealed that participants seemed to prefer non-minimalist graphs [Levy et al, 1996;Inbar et al, 2007], e.g., for showing information to others. They also found that adding "visual difficulties" might enhance comprehension of the data [Hullman et al, 2011;Borgo et al, 2012].…”
Section: Perception and Data Representationmentioning
confidence: 98%